Taxation of a lawyer’s income in Ukraine and the Republic of Poland: comparative legal characteristics - Borshchevskyy, Oleh (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The legal regulation of income taxation of self-employed persons in Ukraine is undergoing a new stage of discussion and establishment. In this long discussion, new arguments arise, taking into account the emerging pandemic and the started war against Ukraine. To support business entities, the Ukrainian legislator resorted to reducing the tax rate for some categories of entrepreneurs who are on the simplified taxation system. For self-employed persons who pay tax on net income minus expenses, the expenses include money voluntarily transferred to the Armed Forces of Ukraine, other military formations, military units, and units. These are approaches that will help increase defense capability and create conditions for supporting entrepreneurship during martial law. At the same time, the question of creating favorable tax conditions for self-employed persons, who form the income part of the budget with their work, remains open. The group of self-employed persons includes lawyers who are on the general taxation system and cannot switch to the simplified one, since the current legislation does not provide for such a right. The Bar also operates in the Republic of Poland, where lawyers, as well as in Ukraine, provide legal assistance and ensure the protection of rights and representation of interests in court. But today, a lawyer in Poland has the right to choose the taxation system. The legal regulation of taxation of the lawyer’s income and ensuring the right to choose the taxation system has an impact on ensuring the independence of the legal profession and its self-governing development. Therefore, the purpose of this article is to carry out a comparative legal characterization between the approaches and legal regulation of the taxation of the lawyer’s income in Ukraine and the Republic of Poland, to reveal their features and to carry out an analysis of draft laws in Ukraine in this area.